REKONSTRUKSI TANGGUNG JAWAB KORPORASI RUMAH SAKIT DALAM FILTRASI KOMPETENSI TENAGA MEDIS: ANALISIS DELIK KELALAIAN PADA REZIM SURAT TANDA REGISTRASI SEUMUR HIDUP - Yudhi Hertanto; Ady Purwoto (The Juris, 2026)
The transformation of health law through Law Number 17 of 2023 has introduced a radical shift by implementing a lifetime Registration Certificate (STR). This change fundamentally shifts the weight of competency oversight from professional organizations to the government and healthcare facilities. This research aims to analyze the legal accountability mechanisms of hospitals in periodically verifying the competence of medical personnel, as well as the limits of corporate liability in cases of malpractice by doctors whose competencies are outdated. The research method used is normative juridical with statutory and conceptual approaches. The results indicate that in the era of the lifetime STR, competency verification now relies on the Practice License (SIP) renewal cycle via the SATUSEHAT platform and internal hospital re-credentialing mechanisms. Based on the doctrine of Corporate Negligence and Article 193 of Law No. 17 of 2023, hospitals bear systemic legal responsibility for failures in performing clinical oversight functions. Hospitals can no longer hide behind the status of doctors as independent partners if they are proven negligent in ensuring the technical skill updates of their medical staff.